Turbulence in an inundated urban environment during a major flood: implications in terms of people evacuation and sediment deposition. (22nd May 2014) - Chanson, H.; Brown, R.
<x content-type="archive" xml:space="preserve">Abstract</x> Floods through inundated urban environments constitute a hazard to the population and infrastructure. A series of field measurements were performed in an inundated section of the City of Brisbane (Australia) during a major flood in January 2011. Using an acoustic Doppler velocimeter (ADV), detailed velocity and suspended sediment concentration measurements were conducted about the peak of the flood. The results are discussed with a focus on the safety of individuals in floodwaters and the sediment deposition during the flood recession. The force of the floodwaters in Gardens Point Road was deemed unsafe for individual evacuation. A comparison with past laboratory results suggested that previous recommendations could be inappropriate and unsafe in real flood flows.